Method for improving photoelectric conversion efficiency of perovskite solar cell based on long-chain alkylamine salt

By using multifunctional group sulfonic acid long-chain alkyl amine salt materials in perovskite solar cells, the growth process of perovskite materials is optimized, and the problem of improving photoelectric conversion efficiency and defect state density in the prior art is solved, and more efficient photoelectric conversion efficiency and fill factor are achieved.

CN119707705APending Publication Date: 2025-03-28HUBEI WONDER SOLAR LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411795321.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing perovskite solar cells have limitations in improving photoelectric conversion efficiency, especially in the regulation of material components and crystallization optimization, which is difficult to effectively reduce defect state density and improve fill factor.

Method used

The sulfonic acid long-chain alkylamine salt material with polyfunctional groups is used to optimize the growth process of perovskite materials in the mesoporous framework by combining with the TiO2 and ZrO2 frameworks and acting as nucleation sites in the perovskite, thereby improving crystallization quality and reducing defect state density.

Benefits of technology

It significantly improves the photoelectric conversion efficiency of perovskite solar cells, improves the filling factor and open circuit voltage, and reduces the non-radiative recombination during the device's operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707705A_ABST
    Figure CN119707705A_ABST
Patent Text Reader

Abstract

The invention provides a method for improving the photoelectric conversion efficiency of a perovskite solar cell based on long-chain alkylamine salt. The perovskite solar cell comprises a perovskite active layer, and the perovskite active layer comprises a perovskite material and a long-chain alkylamine salt material. The long-chain alkylamine salt material comprises at least one of a first material and a second material, the first material has a structure as shown in a formula (1), the second material has a structure as shown in a formula (2): # imgabs0 #, and R1 is selected from substituted or unsubstituted C8-18 alkyl, substituted or unsubstituted C8-18 alkenyl and substituted or unsubstituted C8-18 alkynyl; r2 is selected from a substituted or unsubstituted C1-4 alkyl group, a substituted or unsubstituted amino group, and a substituted or unsubstituted 5-to 6-membered heterocyclic group; and R3 is selected from H, substituted or unsubstituted C1-4 alkyl, and substituted or unsubstituted amino. The photoelectric conversion efficiency of the provided perovskite solar cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of perovskite solar cells, and in particular to a method for improving the photoelectric conversion efficiency of perovskite solar cells based on long-chain alkylamine salts. Background Art

[0002] As a free and sustainable energy source, solar energy has become a hot topic of research. Among the developed solar energy utilization technologies, photovoltaic (PV) power generation technology based on solar cells converts solar energy into directly usable electrical energy, which has the most development prospects. Perovskite solar cells have become a research hotspot in the photovoltaic field due to their high photoelectric conversion efficiency, low cost and easy preparation. With the continuous efforts of researchers, the efficiency of PSCs has been continuously improved. So far, the highest certified efficiency of PSCs has reached 26.7%.

[0003] Additive materials have been widely used to improve the crystallization quality of perovskite films and further enhance the photoelectric conversion efficiency of perovskite solar cells. Additive materials can achieve the purpose of depositing high-quality perovskite films on substrates by affecting the binding form between solutes and solvents in precursor solutions, changing the precipitation process of solutes, or improving the affinity between substrates and precursor solutions. Developing new additive materials to improve the crystallization quality of perovskite crystals and reduce the defect state density is an important technical means to obtain efficient and stable perovskite solar cells. Summary of the invention

[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.

[0005] Perovskite solar cells have received widespread attention in recent years due to their low cost, high efficiency, and high theoretical efficiency limit. In recent years, the commercialization process in the perovskite field has accelerated, and the industrial chain has been gradually improved. In July 2024, its efficiency has been increased to 26.7%. The improvement of the performance of perovskite solar cells is inseparable from the regulation of material components and crystallization optimization. Additive engineering is a method widely used to regulate the material components and crystallization of perovskite solar cells. Its main mechanism is to use the functional groups in the molecules of additive materials to combine with perovskites. For example, it combines with perovskite surface defects to passivate the surface defects of perovskite crystals, reduce non-radiative conformity, and improve the photoelectric conversion efficiency of the device. Or it can be combined with the surface of perovskite microcrystals to change the crystal growth path and optimize the crystallization process to improve the crystal quality and device performance. The present invention provides a -SO3 - or -COO - 、-NH3 + The multifunctional sulfonic acid long-chain alkylamine salt materials are used to improve the photoelectric conversion efficiency of perovskite solar cells. On the one hand, such materials can be combined with TiO2 and ZrO2 skeletons, and on the other hand, the -NH3+ It can act as a nucleation site for perovskite, thereby achieving uniform nucleation and growth of perovskite in the mesoporous skeleton, and realizing the preparation of high-quality perovskite films in the mesoporous skeleton, thereby reducing the defect state density in the perovskite crystal, improving the filling factor and open circuit voltage of perovskite solar cells, and thus improving the photoelectric conversion efficiency of perovskite solar cells.

[0006] Specifically, the present invention provides the following technical solutions:

[0007] A first aspect of the present invention provides a long-chain alkylamine salt material for a perovskite solar cell, wherein the long-chain alkylamine salt material comprises at least one of a first material and a second material, wherein the first material has a structure shown in formula (1), and the second material has a structure shown in formula (2):

[0008]

[0009]

[0010] Wherein R1 is selected from substituted or unsubstituted C 8-18 Alkyl, substituted or unsubstituted C 8-18 Alkenyl, substituted or unsubstituted C 8-18 Alkynyl;

[0011] R2 is selected from substituted or unsubstituted C 1-4 Alkyl, substituted or unsubstituted amino, substituted or unsubstituted 5- to 6-membered heterocyclic group;

[0012] R3 is selected from H, substituted or unsubstituted C 1-4 Alkyl, substituted or unsubstituted amino.

[0013] According to an embodiment of the present invention, R1 is selected from substituted or unsubstituted C 8-18 Alkyl, substituted or unsubstituted C 8-18 Alkenyl, substituted or unsubstituted C 8-18 Alkynyl, the C 8-18 Alkyl, C 8-18 Alkenyl, C 8-18 The alkynyl group may be independently substituted by one or more alkyl, alkenyl, alkynyl, halogen, aryl, or heteroaryl groups;

[0014] R2 is selected from substituted or unsubstituted C 1-4 alkyl, substituted or unsubstituted amino, substituted or unsubstituted 5- to 6-membered heterocyclic group, the C 1-4 Alkyl, amino, 5- to 6-membered heterocyclic groups may be independently substituted by one or more alkyl, alkenyl, alkynyl, hydroxyl, halogen, aryl, heteroaryl, heterocyclic groups;

[0015] R3 is selected from substituted or unsubstituted C 1-4 Alkyl, substituted or unsubstituted amino, the C 1-4 The alkyl group and the amino group may be independently substituted by one or more alkyl groups, alkenyl groups, alkynyl groups, halogen groups, aryl groups, heteroaryl groups, and heterocyclic groups.

[0016] According to an embodiment of the present invention, the R1 is selected from C 8-18 Alkyl, C 8-18 alkenyl;

[0017] R2 is selected from substituted or unsubstituted C 1-4 Alkyl, substituted or unsubstituted amino, the C 1-4 The alkyl group and the amino group may be independently substituted by one or more alkyl groups, alkenyl groups, alkynyl groups, hydroxyl groups, halogen groups, or 5- to 6-membered heterocyclic groups;

[0018] R3 is selected from substituted or unsubstituted C 1-4 Alkyl, the C 1-4 The alkyl group may be substituted by one or more alkyl groups, halogen groups, or aryl groups.

[0019] According to an embodiment of the present invention, the R1 is selected from -(CH2)7CH3, -(CH2)8CH3, -(CH2)9CH3, -(CH2) 10 CH3, -(CH2) 11 CH3, -(CH2) 12 CH3, -(CH2) 13 CH3, -(CH2) 14 CH3, -(CH2) 15 CH3, -(CH2) 16 CH3, -(CH2) 17 CH3, -(CH2)5CH=CH(CH2)7CH3, -(CH2)6CH=CH(CH2)7CH3, -(CH2)7CH=CH(CH2)7CH3, -(CH2)7CH =CH(CH2)8CH3, -(CH2)8CH=CH(CH2)7CH3, -(CH2)7CH=CH(CH2)6CH3, or -(CH2)7CH=CH(CH2)5CH3;

[0020] The R2 is selected from -CH3, -C2H5, -C3H7, -C2H4OH, -CF3, -(CF2)3CF3, -NH2, -NHCH3,

[0021]

[0022] The R3 is selected from -H, -CH3, -CF3, -(CF2)3CF3.

[0023] According to an embodiment of the present invention, the long-chain alkylamine salt material is selected from at least one of the following:

[0024]

[0025]

[0026]

[0027] A second aspect of the present invention provides a perovskite solar cell, comprising a perovskite active layer, wherein the perovskite active layer comprises a perovskite material and the long-chain alkylamine salt material according to any one of the first aspects.

[0028] According to an embodiment of the present invention, the molar ratio of the long-chain alkylamine salt material to the perovskite material is (0.01-1): 1. According to a preferred embodiment, the molar ratio of the long-chain alkylamine salt material to the perovskite material is (0.05-0.5):1.

[0029] A third aspect of the present invention provides a perovskite solar cell, comprising:

[0030] Conductive substrate;

[0031] A dense layer, the dense layer is disposed on the conductive substrate;

[0032] A mesoporous electron transport layer, wherein the mesoporous electron transport layer is located on the dense layer;

[0033] A mesoporous spacer layer, wherein the mesoporous spacer layer is disposed on the mesoporous electron transport layer;

[0034] A porous counter electrode layer, wherein the porous counter electrode layer is disposed on the mesoporous spacer layer;

[0035] and a perovskite active layer, wherein the perovskite active layer is filled in the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer, and the long-chain alkylamine salt material described in any one of the first aspects is added to the perovskite active layer.

[0036] According to an embodiment of the present invention, the conductive substrate is selected from one or more of FTO conductive glass, ITO conductive glass, PET / ITO conductive glass, and PEN / ITO conductive glass;

[0037] The material of the dense layer is selected from one or more of TiO2, SnO2, ZnO, BaSnO3, and SrTiO3;

[0038] The material of the mesoporous electron transport layer is selected from one or more of TiO2, SnO2, ZnO, BaSnO3, and SrTiO3;

[0039] The material of the mesoporous spacer layer is selected from one or more of ZrO2, SiO2, Al2O3, and BaTiO3;

[0040] The material of the porous counter electrode layer is carbon.

[0041] According to an embodiment of the present invention, the long-chain alkylamine salt material is added to the perovskite precursor solution and is jointly filled in the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer to obtain the perovskite active layer;

[0042] Alternatively, before filling the perovskite precursor solution, a long-chain alkylamine salt is filled into the pore structure of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer, and then the perovskite precursor solution without the long-chain alkylamine salt is filled.

[0043] A fourth aspect of the present invention provides a method for improving the efficiency of a perovskite solar cell, comprising:

[0044] Filling a perovskite solution containing a long-chain alkylamine salt material in the pore structure of a porous counter electrode layer, a mesoporous spacer layer, and a mesoporous electron transport layer of a perovskite solar cell to form a perovskite active layer;

[0045] Alternatively, the method includes filling a long-chain alkylamine salt in the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer before filling the perovskite precursor solution, and then filling the perovskite precursor solution without the long-chain alkylamine salt to form the prepared perovskite active layer;

[0046] The long-chain alkylamine salt material mentioned is the long-chain alkylamine salt material described in the first aspect.

[0047] The beneficial effects achieved by the present invention are at least:

[0048] The present invention adopts a long-chain alkylamine salt material with multiple action sites to optimize the growth process of the perovskite material in the mesoporous skeleton, improve the crystallization quality of the prepared perovskite crystal, improve the light absorption capacity of the perovskite material while reducing the defect state density inside the crystal and at the interface, inhibit non-radiative recombination during the operation of the device, improve the open circuit voltage and fill factor of the device, and ultimately improve the photoelectric conversion efficiency of the perovskite solar cell device.

[0049] The long-chain alkylamine salt molecules provided by the present invention have multiple binding sites, and have strong interactions with the A, B, and X positions in the perovskite material. They can also combine with the TiO2 skeleton and the ZrO2 skeleton to provide nucleation sites, thereby optimizing the perovskite crystal growth process. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 It is the crystal diagram of the control group sample provided according to Example 1 of the present invention.

[0051] Figure 2 It is a crystal diagram of the experimental group samples provided according to Example 1 of the present invention. DETAILED DESCRIPTION

[0052] Embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0053] The present invention provides a long-chain alkylamine salt material having -NH3 + 、-SO3 - The two action sites can interact significantly with the A and B sites in the perovskite, passivate the uncoordinated metal ions, dangling bonds and other defects on the surface of the perovskite, thereby improving the device open circuit and filling factor; can combine with the TiO2 skeleton to provide nucleation sites, optimize the crystallization process of the perovskite crystal, thereby improving the short-circuit current of the device, and be used to prepare perovskite solar cells to improve the photoelectric conversion efficiency of perovskite solar cells. The structure of this type of material is shown in the following formula (1):

[0054]

[0055] In formula (1), R1 is selected from substituted or unsubstituted C 8-18 Alkyl, substituted or unsubstituted C 8-18 Alkenyl, substituted or unsubstituted C 8-18 Alkynyl;

[0056] R2 is selected from substituted or unsubstituted C 1-4 an alkyl group, a substituted or unsubstituted amino group, or a substituted or unsubstituted 5- to 6-membered heterocyclic group.

[0057] The present invention also provides a long-chain alkylamine salt material, which has -NH3 + 、-CO2 - The two action sites can interact significantly with the A and B sites in the perovskite, passivate the uncoordinated metal ions, dangling bonds and other defects on the surface of the perovskite, thereby improving the device open circuit and filling factor; can combine with the TiO2 skeleton to provide nucleation sites, optimize the crystallization process of the perovskite crystal, thereby improving the short-circuit current of the device, and be used to prepare perovskite solar cells to improve the photoelectric conversion efficiency of perovskite solar cells. The structure of this type of material is shown in the following formula (2):

[0058]

[0059] In formula (1), R1 is selected from substituted or unsubstituted C 8-18 Alkyl, substituted or unsubstituted C 8-18 Alkenyl, substituted or unsubstituted C 8-18 Alkynyl;

[0060] R3 is selected from H, substituted or unsubstituted C 1-4 Alkyl, substituted or unsubstituted amino.

[0061] Of the two materials of formula (1) or formula (2), only one of the materials can be selected to be added to prepare a perovskite solar cell, or two or more materials can be selected to be added simultaneously to prepare a perovskite solar cell. When two or more materials are selected to be added, they can be respectively from the structure shown in formula (1), or respectively from the structure shown in formula (2), or from the structures shown in formula (1) and formula (2). Specifically, when using the materials shown in the above formula (1) or formula (2), the R1 groups can be the same or different, and can be selected as needed.

[0062] According to a specific embodiment, the R1 is selected from substituted or unsubstituted C 8-18 Alkyl, substituted or unsubstituted C 8-18 Alkenyl, substituted or unsubstituted C 8-18 Alkynyl, the C 8-18 Alkyl, C 8-18 Alkenyl, C 8-18 The alkynyl group may be independently substituted by one or more alkyl, alkenyl, alkynyl, halogen, aryl, heteroaryl. 8-18 Alkyl, C 8-18 According to a more preferred embodiment, R1 is selected from -(CH2)7CH3, -(CH2)8CH3, -(CH2)9CH3, -(CH2) 10 CH3, -(CH2) 11 CH3, -(CH2) 12 CH3, -(CH2) 13 CH3, -(CH2) 14 CH3, -(CH2) 15 CH3, -(CH2) 16 CH3, -(CH2) 17 CH3, -(CH2)5CH=CH(CH2)7CH3, -(CH2)6CH=CH(CH2)7CH3, -(CH2)7CH=CH(CH2)7CH3, -(CH2)7CH =CH(CH2)8CH3, -(CH2)8CH=CH(CH2)7CH3, -(CH2)7CH=CH(CH2)6CH3, or -(CH2)7CH=CH(CH2)5CH3.

[0063] According to a specific embodiment, said R2 is selected from substituted or unsubstituted C 1-4 alkyl, substituted or unsubstituted amino, substituted or unsubstituted 5- to 6-membered heterocyclic group, the C 1-4 The alkyl, amino, 5- to 6-membered heterocyclic group may be independently substituted by one or more alkyl, alkenyl, alkynyl, hydroxyl, halogen, aryl, heteroaryl, heterocyclic group. According to a preferred embodiment, R2 is selected from substituted or unsubstituted C 1-4 Alkyl, substituted or unsubstituted amino, the C 1-4 The alkyl and amino groups may be independently substituted by one or more alkyl, alkenyl, alkynyl, hydroxyl, halogen, 5- to 6-membered heterocyclic groups. According to a more preferred embodiment, the R2 is selected from -CH3, -C2H5, -C3H7, -C2H4OH, -CF3, -(CF2)3CF3, -NH2, -NHCH3,

[0064] According to a specific embodiment, R3 is selected from substituted or unsubstituted C 1-4 Alkyl, substituted or unsubstituted amino, the C 1-4 The alkyl and amino groups may be independently substituted by one or more alkyl, alkenyl, alkynyl, halogen, aryl, heteroaryl, or heterocyclic groups. 1-4 Alkyl, substituted or unsubstituted amino, the C 1-4 The alkyl and amino groups can be substituted independently by one or more alkyl, alkenyl, alkynyl, hydroxyl, halogen, 5-6 membered heterocyclic groups. According to a more preferred embodiment, the R3 is selected from -H, -CH3, -CF3, -(CF2)3CF3.

[0065] The halogen mentioned can specifically be fluorine, chlorine, bromine, iodine, etc. Herein, "alkyl" includes a carbon atom saturated straight chain or branched monovalent alkyl group, wherein the alkyl group can be independently optionally substituted with one or more substituents described in the present invention. According to some embodiments, the alkyl group contains 8-18 carbon atoms, and according to other embodiments, the alkyl group contains 10-18 carbon atoms. The alkyl group used as a substituent can be 1 to 10 carbon atoms, for example, 1 to 8 carbon atoms, 1 to 7 carbon atoms, 1 to 6 carbon atoms, 1 to 5 carbon atoms, 1 to 4 carbon atoms, etc. Including but not limited to methyl (-CH3), ethyl (-CH2CH3), n-propyl (-CH2CH2CH3), isopropyl (-CH(CH3)2), n-butyl (-CH2CH2CH2CH3), 2-methylpropyl or isobutyl (-CH2CH(CH3)2), 1-methylpropyl or sec-butyl (-CH(CH3)CH2CH3), tert-butyl (-C(CH3)3) and the like.

[0066] Alkenyl refers to a hydrocarbon group containing at least one carbon-carbon double bond. It can be a straight chain, branched or cyclic structure. According to some embodiments, the alkenyl group contains 8-18 carbon atoms, and according to other embodiments, the alkenyl group contains 10-18 carbon atoms. The alkenyl group used as a substituent can be 2 to 10 carbon atoms, for example, 2 to 8 carbon atoms, 2 to 7 carbon atoms, 2 to 6 carbon atoms, 2 to 5 carbon atoms, 2 to 4 carbon atoms, etc.

[0067] Alkynyl refers to a hydrocarbon group containing at least one carbon-carbon triple bond. It can be a straight chain, branched chain or cyclic structure. According to some embodiments, the alkynyl group contains 8-18 carbon atoms, according to other embodiments, the alkynyl group contains 10-18 carbon atoms. The alkynyl group used as a substituent can be 2 to 10 carbon atoms, for example, 2 to 8 carbon atoms, 2 to 7 carbon atoms, 1 to 6 carbon atoms, 2 to 5 carbon atoms, 2 to 4 carbon atoms, etc.

[0068] The term "aryl" may be a monocyclic, bicyclic, and tricyclic carbon ring system, wherein at least one ring system is aromatic, wherein each ring system contains 3-7 atoms and has only one point of attachment to the rest of the molecule. The term "aryl" may be used interchangeably with the term "aromatic ring", such as an aromatic ring may include a phenyl group. Depending on the structure, an aryl group may be a monovalent group or a divalent group, i.e., an arylene group. An aryl group may be substituted with other substituents as described herein.

[0069] The term "heteroaryl" refers to a monocyclic ring system in which one or more atoms of the heteroaryl ring are independently optionally substituted by heteroatoms (heteroatoms selected from N, O, P, S, where S or P is independently optionally substituted by one or more oxygen atoms to give groups such as SO, SO2, PO, PO2). The heteroaryl system can be attached to the main structure at any heteroatom or carbon atom to form a stable compound.

[0070] The term "heterocyclyl" or "heterocycle" refers to a monocyclic ring system in which one or more atoms in the ring are independently optionally replaced by heteroatoms, and the ring may be fully saturated or contain one or more unsaturations, but is never aromatic. The heterocyclic ring system may be attached to the main structure at any heteroatom or carbon atom to form a stable compound. The heteroatoms mentioned include, but are not limited to, O, N, S, etc. According to a specific embodiment, the heterocyclic group mentioned is a 5- to 6-membered heterocyclic group.

[0071] The present invention also provides a perovskite solar cell, comprising:

[0072] Conductive substrate;

[0073] A dense layer, the dense layer is disposed on the conductive substrate;

[0074] A mesoporous electron transport layer, wherein the mesoporous electron transport layer is located on the dense layer;

[0075] A mesoporous spacer layer, wherein the mesoporous spacer layer is disposed on the mesoporous electron transport layer;

[0076] A porous counter electrode layer, wherein the porous counter electrode layer is disposed on the mesoporous spacer layer;

[0077] and a perovskite active layer, wherein the perovskite active layer is filled in the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer, and the long-chain alkylamine salt material mentioned above is added to the perovskite active layer.

[0078] Among them, the conductive substrate can choose a variety of materials, such as FTO conductive glass, ITO conductive glass, PET / ITO conductive glass, PEN / ITO conductive glass. For example, indium tin oxide (ITO) or fluorine-doped tin oxide (FTO) glass can be used as the substrate of the battery to provide good optical transparency and conductivity. The dense layer is located on the conductive substrate layer, and the commonly used dense layer materials include but are not limited to TiO2, SnO2, ZnO, BaSnO3, SrTiO3, etc. Commonly used mesoporous electron transport layer materials include TiO2, SnO2, ZnO, BaSnO3, SrTiO3, etc. These materials are used to efficiently transfer electrons to the electrode and prevent holes from being transmitted to the cathode. The materials that can be used as mesoporous spacer layers are usually some inorganic oxide materials (such as SiO2, ZrO2, Al2O3). These materials play a role of isolation and protection in perovskite solar cells, and also help to improve the performance of the battery. For example, SiO2 and ZrO2 are often used as spacer layer materials. The spacer layer film prepared by SiO2@ZrO2 nanoparticles has the characteristics of ultra-flatness and crack-free, which can effectively improve the power conversion efficiency of perovskite solar cells. In addition, Al2O3 is also widely used in spacer layer materials, especially when used in combination with ZrO2, which can significantly improve the photoelectric conversion efficiency. According to a specific embodiment, the mesoporous spacer layer material includes but is not limited to ZrO2, SiO2, Al2O3, BaTiO3. The material of the porous counter electrode layer is a carbon material.

[0079] The perovskite active layer is filled in the pore structure of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer. The perovskite active layer includes a perovskite material and the long-chain alkylamine salt material mentioned. The perovskite material mentioned is usually composed of a perovskite material with an ABX3 structure, such as methylamine lead iodine (CH3NH3PbI3), methylamine lead bromide (MAPbBr3), formamidine lead iodine (FAPbI3), formamidine lead bromide (FAPbBr3), cesium lead iodine (CsPbI3), cesium lead bromide (CsPbBr3), methylamine tin iodine (MASnI3), methylamine tin bromide (MASnBr3) and mixed cations, anions and perovskite materials and the like. The perovskite material and the sulfonic acid long-chain alkylamine salt material can be added dropwise to the mesoporous structure, left to stand for a period of time, and annealed on a hot stage at 50-80°C for 1-10 hours (according to a preferred embodiment, annealing can be performed at a temperature of 60°C for 1 hour).

[0080] The perovskite solar cell mentioned above can be obtained by a preparation method commonly used in the art.

[0081] According to a specific implementation, the long-chain alkylamine salt material is added to the perovskite precursor solution and is jointly filled in the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer to obtain the perovskite active layer.

[0082] According to a specific embodiment, long-chain alkylamine salts may be filled into the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer before filling the perovskite precursor solution, and then the perovskite precursor solution without long-chain alkylamine salts may be filled.

[0083] Compared with the case where the material mentioned in the present invention is not added, the addition of long-chain alkylamine salt material can increase the photoelectric conversion efficiency of the perovskite solar cell by up to 10%, 15%, or even more than 20%.

[0084] The technical solution of the present invention is described below by specific examples. It should be noted that these examples are only used to facilitate the understanding of those skilled in the art and should not be regarded as limiting the scope of protection of the present invention. The substances listed in the table of the present invention are used as materials to prepare perovskite solar cells, which have been verified to significantly improve the photoelectric conversion efficiency of perovskite solar cells. Unless otherwise specified, the reagents used in the examples can be obtained by commercial purchase or synthesis in combination with the common sense of those skilled in the art.

[0085] Example 1

[0086] Example 1 Taking trifluoromethanesulfonic acid oleyl primary amine as an example, a perovskite solar cell was prepared.

[0087] The specific steps include:

[0088] (1) Glass substrate processing: mainly includes three steps: cutting / laser etching and cleaning.

[0089] Cutting: Use a glass cutter to cut the original glass into the required size. Before cutting, make sure the glass surface is clean to avoid defects during the cutting process. After cutting, grind the glass to smooth the sharp edges.

[0090] Laser etching: Use laser etching equipment to adjust the laser power and parameters to control the etching depth and accuracy, and perform high-precision processing on the glass substrate. Laser etching can remove part of the material to form the desired pattern or structure.

[0091] Cleaning: After cutting and laser etching, the glass substrate is cleaned in an ultrasonic cleaner using deionized water and detergent for multiple rounds to remove residual impurities and contaminants. After cleaning, it is spun or dried to ensure that there is no residual moisture on the surface.

[0092] (2) Preparation of dense layer and printing and sintering of three-layer film. The diisopropyl di(acetylacetonate)titanate solution is atomized and sprayed on the FTO surface of the above-mentioned glass, and decomposed at high temperature to obtain a dense TiO2 dense layer, which is then cooled naturally; then, a titanium dioxide electron transport layer, a zirconium dioxide spacer layer, and a carbon counter electrode layer are deposited on the glass sprayed with the dense layer by printing layer by layer, and sintered at different temperatures.

[0093] Specifically, a nano-titanium dioxide electron transport layer is deposited on the dense TiO2 layer using screen printing technology, and the pore-forming agent is removed to form a mesoporous titanium dioxide film.

[0094] A zirconium dioxide layer is formed on the mesoporous titanium dioxide film by using a screen printing technique, and then dried at 70° C. to remove the solvent, thereby forming a zirconium dioxide film.

[0095] Finally, a carbon counter electrode layer is deposited on the zirconium dioxide film, usually by screen printing or doctor blade technology, and sintered at an appropriate temperature to ensure its stability.

[0096] (3) Prepare perovskite solution.

[0097] The experiment was divided into a control group and an experimental group.

[0098] Control group: 2.00 g (30 mmol) of methylammonium chloride, 0.796 g (5 mmol) of iodomethylamine, 0.86 g (5 mmol) of formamidine hydroiodide, and 9.22 g (20 mmol) of lead iodide were dissolved in a mixed solvent of 12800 uL of N, N-dimethylformamide (DMF) and 3200 uL of dimethyl sulfoxide (DMSO) to obtain the perovskite precursor solution of the control group.

[0099] Experimental group: oleylamine trifluoromethanesulfonate (added amount is 1 mmol) was additionally added to the precursor perovskite solution of the control group to obtain the precursor solution of the experimental group.

[0100] The precursor solutions of the control group and the experimental group were stirred at 50° C. for 2 h to obtain the control group perovskite solution and the experimental group perovskite solution, respectively.

[0101] (4) Filling of perovskite solution and growth of crystals: First, cover the non-filled area with tape, then use a pipette to transfer the prepared perovskite solution and drop it on the surface of the carbon film. After standing for a certain period of time, place it on a hot stage at 100°C to remove the solvent. The battery preparation process is completed.

[0102] The PCE performance tests were performed on the batteries prepared in the control group and the experimental group respectively.

[0103] The PCE test of solar cells is carried out by combining a solar simulator and a digital source meter efficiency test system to obtain the JV curve of the test device. Before the test, a standard silicon cell must be used as a reference and the calibrated light intensity must be 1 standard sunlight (AM1.5 G, 100mW / cm 2 ). PCE (photovoltaic conversion efficiency) refers to the efficiency of solar cells in converting received light energy into electrical energy, and is a key indicator for measuring battery performance. PCE is composed of V OC , J SC and FF jointly determine. OC (Open circuit voltage) refers to the voltage difference between the two ends of a solar cell when the external circuit is disconnected. SC (Short-circuit current density) refers to the current density under short-circuit conditions. FF (fill factor) refers to the maximum power point voltage (V MP ) and open circuit voltage (V OC ) and maximum power point current (J MP ) product of .

[0104] Table 1 below is a comparison of the average performance of batteries in the same batch. The crystal diagrams of the control group and experimental group batteries are shown in Table 1. Figure 1 and Figure 2 shown. Figure 1 This is the crystallization condition of the control group samples provided in the embodiments of the present invention. It can be found that there is obvious crystal discontinuity in the perovskite inside the device. Figure 2 This is the crystallization condition of the samples in the experimental group provided according to the embodiments of the present invention. It can be found that the perovskite crystals inside the device are continuous and there are almost no cracks.

[0105] Table 1 Performance characterization results

[0106]

[0107] It can be seen from Table 1 above that the perovskite solar cell provided by the present invention can improve the V OC , J SC , FF, thereby improving the photoelectric conversion efficiency of the device.

[0108] Example 2

[0109] Example 2 takes octyl primary amine methanesulfonate as an example to provide a method for preparing a perovskite solar cell.

[0110] The device preparation process is the same as above. The control group perovskite precursor solution is the same as the control group used in the above Example 1; the experimental group is to add methanesulfonic acid octyl primary amine (addition amount is 1 mmol) to the above control group perovskite precursor solution. The control group and the experimental group precursor solutions are stirred at 50°C for 2 hours and then retained for use, respectively obtaining the control group perovskite solution and the experimental group perovskite solution. After characterization, the performance of the prepared control group and experimental group perovskite solar cells is shown in Table 2 below:

[0111] Table 2 Performance characterization results

[0112]

[0113] It can be seen from Table 2 above that the perovskite solar cell provided by the present invention can improve the V OC , J SC , FF, thereby improving the photoelectric conversion efficiency of the device.

[0114] Example 3

[0115] Example 3 takes oleyl primary amine morpholineethanesulfonic acid as an example to provide a method for preparing a perovskite solar cell.

[0116] The preparation process of the perovskite solar cell mentioned is the same as that in Example 1. The perovskite precursor solution of the control group is the same as that in Example 1. The experimental group is prepared by adding a certain amount of oleyl primary amine morpholineethanesulfonate (1 mmol) to the perovskite precursor solution of the control group. The precursor solutions of the control group and the experimental group are stirred at 50°C for 2 hours and then retained for use to obtain the perovskite solution of the control group and the perovskite solution of the experimental group, respectively.

[0117] The performance of the perovskite solar cells in the control group and the experimental group are shown in Table 3:

[0118] Table 3 Performance characterization results

[0119]

[0120] It can be seen from Table 3 above that the perovskite solar cell provided by the present invention can improve the V OC , J SC , FF, thereby improving the photoelectric conversion efficiency of the device.

[0121] Example 4

[0122] Example 4 takes ethanesulfonic acid dodecylamine as an example to provide a method for preparing a perovskite solar cell.

[0123] The preparation process of the perovskite solar cell mentioned is the same as that in Example 1. The perovskite precursor solution of the control group is the same as that in Example 1. The experimental group is pre-filled with an ethanol solution dissolved with 10 mg / ml ethanesulfonic acid dodecylamine before filling the perovskite solution, and then annealed at 60°C to remove the solvent, and then filled with the perovskite precursor solution of the control group in Example 1.

[0124] The performance of the perovskite solar cells in the control group and the experimental group are shown in Table 4:

[0125] Table 4 Performance characterization results

[0126]

[0127]

[0128] It can be seen from Table 4 above that the perovskite solar cell provided by the present invention can improve the V OC , J SC , FF, thereby improving the photoelectric conversion efficiency of the device.

[0129] In the description of this specification, the description with reference to the terms "embodiment", "some embodiments", "specific implementation methods", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example.

[0130] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A long-chain alkylamine salt material for perovskite solar cells, characterized in that: The long-chain alkylamine salt material includes at least one of a first material and a second material, wherein the first material has a structure shown in formula (1), and the second material has a structure shown in formula (2): Wherein R1 is selected from substituted or unsubstituted C 8-18 Alkyl, substituted or unsubstituted C 8-18 Alkenyl, substituted or unsubstituted C 8-18 Alkynyl; R2 is selected from substituted or unsubstituted C 1-4 Alkyl, substituted or unsubstituted amino, substituted or unsubstituted 5- to 6-membered heterocyclic group; R3 is selected from H, substituted or unsubstituted C 1-4 Alkyl, substituted or unsubstituted amino.

2. The long-chain alkylamine salt material for perovskite solar cells according to claim 1, characterized in that: The R1 is selected from substituted or unsubstituted C 8-18 Alkyl, substituted or unsubstituted C 8-18 Alkenyl, substituted or unsubstituted C 8-18 Alkynyl, the C 8-18 Alkyl, C 8-18 Alkenyl, C 8-18 The alkynyl group may be independently substituted by one or more alkyl, alkenyl, alkynyl, halogen, aryl, or heteroaryl groups; R2 is selected from substituted or unsubstituted C 1-4 alkyl, substituted or unsubstituted amino, substituted or unsubstituted 5- to 6-membered heterocyclic group, the C 1-4 Alkyl, amino, 5- to 6-membered heterocyclic groups may be independently substituted by one or more alkyl, alkenyl, alkynyl, hydroxyl, halogen, aryl, heteroaryl, heterocyclic groups; R3 is selected from substituted or unsubstituted C 1-4 Alkyl, substituted or unsubstituted amino, the C 1-4 The alkyl group and the amino group may be independently substituted by one or more alkyl groups, alkenyl groups, alkynyl groups, halogen groups, aryl groups, heteroaryl groups, and heterocyclic groups.

3. The long-chain alkylamine salt material for perovskite solar cells according to claim 1, characterized in that: The R1 is selected from C 8-18 Alkyl, C 8-18 alkenyl; R2 is selected from substituted or unsubstituted C 1-4 Alkyl, substituted or unsubstituted amino, the C 1-4 The alkyl group and the amino group may be independently substituted by one or more alkyl groups, alkenyl groups, alkynyl groups, hydroxyl groups, halogen groups, or 5- to 6-membered heterocyclic groups; R3 is selected from substituted or unsubstituted C 1-4 Alkyl, the C 1-4 The alkyl group may be substituted by one or more alkyl groups, halogen groups, or aryl groups.

4. The long-chain alkylamine salt material for perovskite solar cells according to claim 1, characterized in that: The R1 is selected from -(CH2)7CH3, -(CH2)8CH3, -(CH2)9CH3, -(CH2) 10 CH3, -(CH2) 11 CH3, -(CH2) 12 CH3, -(CH2) 13 CH3, -(CH2) 14 CH3, -(CH2) 15 CH3, -(CH2) 16 CH3, -(CH2) 17 CH3, -(CH2)5CH=CH(CH2)7CH3, -(CH2)6CH=CH(CH2)7CH3, -(CH2)7CH=CH(CH2)7CH3, -(CH2)7CH =CH(CH2)8CH3, -(CH2)8CH=CH(CH2)7CH3, -(CH2)7CH=CH(CH2)6CH3, or -(CH2)7CH=CH(CH2)5CH3; The R2 is selected from -CH3, -C2H5, -C3H7, -C2H4OH, -CF3, -(CF2)3CF3, -NH2, -NHCH3, The R3 is selected from -H, -CH3, -CF3, -(CF2)3CF3.

5. The long-chain alkylamine salt material for perovskite solar cells according to claim 1, characterized in that: The long-chain alkylamine salt material is selected from at least one of the following:

6. A perovskite solar cell, characterized in that: Comprising a perovskite active layer, the perovskite active layer comprising a perovskite material and a long-chain alkylamine salt material according to any one of claims 1 to 5; Optionally, the molar ratio of the long-chain alkylamine salt material to the perovskite material is (0.01-1):

1.

7. A perovskite solar cell, characterized in that: include: Conductive substrate; A dense layer, the dense layer is disposed on the conductive substrate; A mesoporous electron transport layer, wherein the mesoporous electron transport layer is disposed on the dense layer; A mesoporous spacer layer, wherein the mesoporous spacer layer is disposed on the mesoporous electron transport layer; A porous counter electrode layer, wherein the porous counter electrode layer is disposed on the mesoporous spacer layer; and a perovskite active layer, wherein the perovskite active layer is filled in the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer, and the long-chain alkylamine salt material according to any one of claims 1 to 5 is added to the perovskite active layer.

8. The perovskite solar cell according to claim 7, characterized in that: The conductive substrate is selected from one or more of FTO conductive glass, ITO conductive glass, PET / ITO conductive glass, and PEN / ITO conductive glass; The material of the dense layer is selected from one or more of TiO2, SnO2, ZnO, BaSnO3, and SrTiO3; The material of the mesoporous electron transport layer is selected from one or more of TiO2, SnO2, ZnO, BaSnO3, and SrTiO3; The material of the mesoporous spacer layer is selected from one or more of ZrO2, SiO2, Al2O3, and BaTiO3; The material of the porous counter electrode layer is carbon.

9. The perovskite solar cell according to claim 7, characterized in that: The long-chain alkylamine salt material is added to the perovskite precursor solution and is jointly filled into the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer to obtain the perovskite active layer; Alternatively, before filling the perovskite precursor solution, the long-chain alkylamine salt material is filled into the pore structure of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer, and then the perovskite precursor solution without long-chain alkylamine salt is filled.

10. A method for improving the efficiency of a perovskite solar cell, characterized in that: The method comprises filling a perovskite solution containing a long-chain alkylamine salt material in the pore structure of a porous counter electrode layer, a mesoporous spacer layer and a mesoporous electron transport layer of a perovskite solar cell to form a perovskite active layer; Alternatively, the method includes filling a long-chain alkylamine salt material in the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer before filling the perovskite precursor solution, and then filling the perovskite precursor solution without the long-chain alkylamine salt to form a perovskite active layer; The long-chain alkylamine salt material is the long-chain alkylamine salt material according to any one of claims 1 to 5.